Acute coronary syndromes in pregnancy: a literature review. (16th April 2023) - Freeman, Amy; Squire, Gareth; Herrey, Anna; Hogrefe, Kai; Allen, Rebecca
Abstract : Key content: Maternal mortality from cardiovascular disease has not improved in almost 20 years; this contrasts to significant sustained improvement in cardiovascular outcomes in the nonpregnant population, particularly regarding acute coronary syndrome (ACS). Many of the women who died in recent MBRRACE‐UK reports presented with cardiac symptoms and signs, but this was not always recognised upon clinical review. The incidence of ACS is increasing alongside advancing maternal age, with an accompanying increased prevalence of typical and pregnancy‐specific cardiac risk factors. Early involvement of senior clinicians and a multidisciplinary approach is crucial for improving maternal outcomes. Counselling women on long term prognosis and implications for future pregnancy is vital. Learning objectives: To be aware of the latest data for ACS in pregnancy, including the changing trends in prevalence of this condition and the suggested reasoning behind this. To understand the various presentations of ACS in pregnancy and its differential diagnosis. To understand the possible investigation and management of ACS in pregnancy in a multidisciplinary setting.